(untitled) (Namibian Journal of Linguistics, Literature and Communication Studies, 2024)
This article explores how social media can be used as a tool to develop the nascent Namibian fashion industry and encourage consumer interest. This research started from the hypothesis that a localised social media platform could be used as a tool to boost industry competitiveness as well as consumer support. The research took on a mixed methods approach where a survey was undertaken, followed by a series of interviews of local fashion industry stakeholders to gain insight into how social media could best serve Namibian fashion. Analysis of results indicates that a localised social media platform could be beneficial for the industry but it is important that such a platform not exclude opportunities of international exposure and networking. Furthermore, for such a platform to work, stakeholders in the Namibian fashion industry will have to embrace the power of influencers on social media, and the idea of ‘co-creation’ with the social media audience.